Screening for Speech Sound Disorders: Validating the ICS in the Icelandic Context - Iðunn Kristínardóttir 1995- (2025)
Objective: Speech sound disorder (SSD) affects a significant proportion of preschool children, often leading to poorer educational and social outcomes. Screening offers an opportunity for early detection of SSD when interventions may be more effective. However, no formal screening is currently being implemented in Iceland. The Intelligibility in Context Scale: Iceland (ICS-ÍS) is a simple parent-report questionnaire, correlated with intelligibility and speech sound production in Icelandic-speaking preschool children. This study aimed to determine the utility of ICS-ÍS as a screening tool for SSD in Icelandic- speaking preschool children. In particular, the study assessed the relationship of ICS-ÍS scores with percentage of consonants correct (PCC) and Sjúkratryggingar Íslands (Icelandic National Health Insurance [SÍ]) error count, a metric defining reimbursement eligibility or care available for children with SSD within the Icelandic healthcare system. Furthermore, the study aimed to determine a cut-off for the optimal sensitivity and specificity of the ICS-ÍS for SSD screening in Icelandic-speaking 4;0-5;5 year-old children. Method: Data for the study was obtained from three prior studies conducted at the Speech and Language Pathology program of the University of Iceland where data on parent reported ICS-ÍS and Málhljóðapróf ÞM (ÞM’s Test of Speech Sound Disorders [MHP]) was available. Correlation between children’s ICS-ÍS scores and (a) PCC scores (N=179) and (b) SÍ error count (N=118) were analyzed. Furthermore, receiver operating characteristic (ROC) curve analysis was performed to determine an ICS-ÍS cut-off for the optimal screening accuracy for SSD considering PCC criteria (below 2 SD) and for reimbursement eligibility considering SÍ criteria. Result: ICS-ÍS was significantly correlated with both PCC (r=0.63) and SÍ error count (r=-0.67), which also were highly correlated with each other (r=-0.91). An ICS-ÍS cut-off of 4.0 was determined to yield the optimal sensitivity and specificity both for SSD by PCC ...